American Independent Cinema Rites of Passage and the Crisis Image - Backman Rogers, Anna 1981- (Edinburgh Studies in Film and Intermediality : ESFI, 2021)
Examines crisis, transition and metamorphosis in American independent cinemaAnna Backman Rogers argues that American independent cinema is a cinema not merely in crisis, but also of crisis. As a cinema which often explores the rite of passage by explicitly drawing on American cinematic heritage, from the teen movie to the western, American independent films deal in images of crisis, transition and metamorphosis, offering a subversive engagement with more traditional modes of representation.Examining films by Gus Van Sant, Jim Jarmusch and Sofia Coppola, this study sets forth that American indie films offer the viewer an 'art experience' within the confines of commercial, narrative cinema by engaging with cinematic time (as a mode of philosophical thought) and foregrounding the inherent 'crisis' of the cinematic image (as the mode of being as change).Key featuresCase studies include: The Virgin Suicides, Elephant, Dead Man, Last Days, Somewhere and Broken Flowers Argues for the relevance and importance of American indie cinema as a mode of 'art' cinema that offers a challenging viewing experience to a broad audience Engages with and develops on recent scholarship on American independent film from a formal perspectiveSituates analysis of indie film within the context of American generic cinematic (and historical) traditions